Influence of Local Original Revenue and Economic Growth on Poverty Rate in Regency/City of Bali Province - Ni Nyoman Yintayani; Anak Agung Gde Mantra Suarjana; Ni Gusti Nyoman Suci Murni (Jurnal Bisnis dan Kewirausahaan, 2019)
The purpose of this study are: (1) To analyze the influence of local original revenue on poverty rate in regencies/cities in Bali Province. (2) To analyze the influence of economic growth on the rate of poverty in regencies/cities in Bali Province. (3) To analyze the influence of local original revenue and economic growth simultaneously on poverty rate in regencies/cities in Bali Province. (4) To analyze the pattern of the relationship between economic growth and poverty rate in regencies/cities in Bali Province. The research sample was taken with purposive sampling technique in accordance with the objectives of the researcher with several considerations. Data collection is done with documentation techniques. The data analysis technique used is multiple regression techniques. The results of data analysis show that the local original revenue has a negative and significant influence on the rate of poverty in the regency/city government in Bali Province. Economic growth has a negative and significant influence on the rate of poverty in the regency/city government in Bali Province. Local original revenue and economic growth simultaneously have a negative and significant influence on poverty rate in regency/city governments in Bali Province. The pattern of the relationship between economic growth and poverty in each regency/city in the Province of Bali shows that the most ideal condition is achieved by the Badung Regency and Denpasar City including the category of regions where Economic Growth is high with a low poverty rate (Quadrant III). While other regencies in Bali Province have not reached ideal conditions.